Avaliação ex–post da sustentabilidade hídrica e da conservação ambiental de perímetros irrigados implantados – o caso do distrito de irrigação Jaguaribe – Apodi (DIJA) - Nunes, Ana Bárbara de Araújo (2006)
The Jaguaribe-Apodi Irrigation District (DIJA), in the state of the Ceará, was founded aimed at producing food and substances cousins, to create jobs in agricultural businesses and urban-rural activities, to increase and to improve the income distribution and to create conditions for the conquest of the citizenship. This Perimeter was implanted in 1987, but the essential services of administration, operation and maintenance were initiated only from 1989. The irrigated area of DIJA is 5.393ha. The irrigation systems are the methods for microsprinkler, drip and central pivot and are planted about sixteen types of cultures. The general objective of this work was to evaluate the hydro - ambiental sustainability of the DIJA. Instruments were applied to characterize the area under study, such as, as physical - chemical and bacteriological analyses of the surface and drinking waters, determination of the WQI, analysis of satellite images for land use detection and change, determination of Christiansen and Distribution Uniformity Coefficients (CUC and CUD) from emitters and soil – water moisture, analysis of the matrix of impacts before and after the implantation of the irrigation district and risk analysis on those factors. The surface water of the DIJA could not complain to class two for the majority of the samples taken over time in the study area. Restrictions were found relation to bacteriological and physical – chemical parameters. Indication of contamination of surface waters from pesticides was not found. In general, untreated surface water registred an WQI value of 83,79, considered good. For the analyzed drinking water sites (treated water), there were restrictions in relation to the bacteriological quality in the three studied sampling sites. These points need to be monitored by the state water facility, to correct the possible problems in order to complain with water quality standards. Comparing the images of 1996 to the one of 2004, it was observed, both visually and quantitatively that there was an increase of the irrigation in the irrigated perimeter irrigated during these years, thus showing the expansion of the irrigated fruit production farms in DIJA. The results of the efficiency of water application in microsprinkler areas have shown that 73% of the analyzed areas were irrigated in deficit; for the drip irrigated areas, the analysis, showed an over irrigation and for central pivot areas, it was observed 50% in deficit and 50% in excess of irrigation. Thus one can conclude on the lack of irrigation scheduling practives on the majority of the studied areas. In terms of the irrigation uniformity it was found that the risk of CUCq and CUDq to be below of the standards was small; The analysis of the matrix of impacts for the present time showed that the trend was the impact to reduce or to remain unchanged and noticed little influence of these when inserted environment measures in the global context. Of the environment point of view, it was observed that in the bio-physic environment, specialty the aquatic and terrestrial environment, were mainly affected in the beginning of the implantation of the Perimeter and go on if measured of control not be applied.